2014
DOI: 10.1111/sms.12172
|View full text |Cite
|
Sign up to set email alerts
|

Variations in jump height explain the between‐sex difference in patellar tendon loading during landing

Abstract: Patellar tendinopathy is the most common overuse knee injury in volleyball, with men reporting more than twice the injury prevalence than women. Although high patellar tendon loading is thought to be a causative factor of patellar tendinopathy, it is unknown whether between-sex variations in landing technique account for differences in patellar tendon loading. It was hypothesized that male volleyball players would display differences in landing technique and would generate higher patellar tendon loading than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
(58 reference statements)
2
2
0
Order By: Relevance
“…Dancers with PFP used excessive effort to jump higher than those without PFP when instructions provided them to keep pace and elegant posture. This finding was similar to previous work indicating that athletes with patellar tendinopathy demonstrated better jump performance than uninjured athletes, particularly during ballistic jumps involving eccentric force generation [22,25,42]. Low pain severity reported by the PFP group could be one of reasons that dancers with PFP demonstrated greater jumping height.…”
Section: Discussion ▼supporting
confidence: 89%
“…Dancers with PFP used excessive effort to jump higher than those without PFP when instructions provided them to keep pace and elegant posture. This finding was similar to previous work indicating that athletes with patellar tendinopathy demonstrated better jump performance than uninjured athletes, particularly during ballistic jumps involving eccentric force generation [22,25,42]. Low pain severity reported by the PFP group could be one of reasons that dancers with PFP demonstrated greater jumping height.…”
Section: Discussion ▼supporting
confidence: 89%
“…The participants performed 3 different landing styles using the dominant lower extremity, which was defined as the limb preferred for the single-legged landing, from a 30-cm box (women) or a 45-cm box (men). The men landed from a greater box height because their jump capacities are often greater than those of women [21][22][23][24] and because we confirmed that recreationally active men and women could successfully perform the 3 landing styles from these box heights. After digitization procedures were performed as described previously, 16 the participants were familiarized with single-legged drop landings until they were comfortable with all styles.…”
Section: Data Collectionsupporting
confidence: 50%
“…In the sport of volleyball, this 0.03 m increase in jump height is deemed functionally meaningful (Sheppard et al., ). We have previously demonstrated that jump height is a critical factor in patellar tendon loading (Janssen et al., 2014a), and male volleyball players with a greater maximal vertical jump ability are more likely to develop patellar tendinopathy compared with players with a lower vertical jump (Visnes et al., ). Therefore, it is possible that an accumulation of repeatedly higher jump heights contributes to the greater patellar tendinopathy prevalence evident in elite male volleyball players, although this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Isokinetic testing can be used to quantify concentric and eccentric quadriceps muscle strength to identify whether between‐participant differences in quadriceps muscle strength exist, and whether they affect a participant's landing technique. Our previous study identified that male volleyball players with greater quadriceps strength were predicted to incur higher patellar tendon loading (Janssen et al., ), and that jump height was the critical factor in patellar tendon loading (Janssen et al., 2014a). Therefore, it is possible that these patellar tendinopathy risk factors may vary between players of different skill levels and help to explain the between‐skill differences in patellar tendinopathy prevalence.…”
mentioning
confidence: 99%